Blow-molded article, toner bottle, method for producing blow-molded article, molded article, and pellet

By adding mineral layers of dihydride and zeolite to the blow molding finished product and including zeolite, the expansion and blow molding process are adopted to solve the problems of high cost and environmental impact of plastic bottle recycling, preventing chemical attacks of toner particles, and improving the uniformity of toner density.

JP2025062997APending Publication Date: 2025-04-15CANON KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024137903
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-03
Filing Date
2024-08-19
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing chemical recycling and material recycling methods have high cost and environmental impact on the recycling of plastic bottles. Especially when cleaning is not carried out or simplified, chemical attacks may occur on the surface of toner particles in the plastic bottles, resulting in uneven toner density and affecting the formation of electro-optical images.

Method used

By adding mineral layer dihydride and zeolite to the blow-molded finished product and including the basin in the finished product, the dilation and blow-molding process is adopted to inhibit the surface transfer of the basin and prevent chemical attacks from toner particles.

Benefits of technology

It effectively prevents the surface transfer of the baton, avoids chemical attacks on the surface of toner particles, ensures the uniformity of toner density, and improves the quality of electro-optical image formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062997000001_ABST
    Figure 2025062997000001_ABST
Patent Text Reader

Abstract

To provide a blow-molded article that is resistant to image defects resulting from chemical attack, even when using wax-contaminated polyethylene or polypropylene.SOLUTION: This blow-molded article includes: at least one selected from the group consisting of an inorganic layered double hydroxide and a zeolite; polyethylene or polypropylene; and a wax.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a blow molded article, a toner bottle, and a method for manufacturing the blow molded article. The present disclosure also relates to a molded article and a pellet. [Background technology]

[0002] Toner bottles that store toner to be supplied to electrophotographic image forming apparatuses are required to have high strength, for example, so that they will not break even when dropped. For this reason, molded products obtained by blow molding polypropylene (hereinafter, sometimes referred to as "PP") are sometimes used. Patent Document 1 discloses a container that is a blow molded product of PP. Also, molded products obtained by blow molding polyethylene (hereinafter, sometimes referred to as "PE") PE are sometimes used. Patent Document 3 discloses a toner container that is a blow molded product of PE.

[0003] In recent years, from the viewpoint of environmental protection, it has become common to collect thermoplastic resin products and their parts, regenerate them by temporarily changing their original shape, and then recycle them. Here, as described in paragraph

[0002] of Patent Document 2, chemical recycling and material recycling are known as methods for recycling thermoplastic resins such as PE or PP. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-178390 A [Patent Document 2] JP 2009-001693 A [Patent Document 3] JP 2010-260638 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, as disclosed in Patent Document 2, chemical recycling requires a multi-stage process, which requires decomposition equipment and purification treatment equipment, resulting in high recycling costs and a large environmental impact. On the other hand, in material recycling, a process of washing bottles is generally performed. However, bottle washing may be performed multiple times using water, acid, alkali, etc., and a drying process is also required. Therefore, bottle washing can also increase the environmental load.

[0006] From the viewpoint of reducing the environmental load, the present inventors simplified or omitted the washing of the toner bottle to be recycled, and produced a toner bottle again using PE or PP obtained from the toner bottle with toner still attached inside. Then, when toner was stored in the toner bottle obtained in this way, it was found that the surface of the toner particles may be deformed at the contact point between the toner in the toner bottle and the inner surface of the toner bottle. Toner particles with a deformed surface may cause development defects, and development defects may cause density unevenness in electrophotographic images.

[0007] At least one aspect of the present disclosure is directed to providing a blow molded article that can prevent the migration of wax to the surface of the blow molded article, assuming that wax-containing polyethylene or polypropylene is used as a raw material. At least one aspect of the present disclosure is directed to providing a toner bottle that can prevent deterioration of the toner contained therein. Furthermore, at least one aspect of the present disclosure is directed to providing a toner bottle that can prevent the migration of wax to the surface of the blow molded article, assuming that wax-containing polyethylene or polypropylene is used as a raw material. The present invention aims to provide a method for producing a blow molded article that can prevent migration of the above-mentioned components. Furthermore, at least one aspect of the present disclosure is directed to providing a molded article that can prevent migration of wax to the surface, assuming that wax-containing polyethylene or polypropylene is used as a raw material. Still further, at least one aspect of the present disclosure is directed to providing pellets that contribute to suppression of wax migration to the surface of a molded article. [Means for solving the problem]

[0008] According to at least one embodiment of the present disclosure, there is provided a blow molded article, comprising: The blow molded article is At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A blow molded article is provided, comprising:

[0009] According to at least one aspect of the present disclosure, there is provided a toner bottle, comprising: The toner bottle is At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A toner bottle is provided, comprising:

[0010] According to at least one embodiment of the present disclosure, there is provided a method for producing the blow molded article, comprising the steps of: A step of preparing a preform containing at least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite, the polyethylene or polypropylene, and the wax; and There is also provided a method for producing a blow-molded article, comprising a molding step of stretch-blow molding the preform to obtain the blow-molded article.

[0011] According to at least one aspect of the present disclosure, there is provided a method for producing the blow molded article, comprising the steps of: preparing pellets containing at least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite, the polyethylene or polypropylene, and the wax; and There is also provided a method for producing a blow-molded article, comprising a molding step of blow-molding the pellets to obtain the blow-molded article.

[0012] Further, according to at least one embodiment of the present disclosure, there is provided a molded article, the molded article comprising: A molded article is provided, comprising at least one selected from the group consisting of an inorganic layered double hydroxide and a zeolite, polyethylene or polypropylene, and a wax.

[0013] Furthermore, according to at least one embodiment of the present disclosure, there is provided a pellet comprising at least one selected from the group consisting of an inorganic layered double hydroxide and a zeolite, polyethylene or polypropylene, and a wax. Effect of the Invention

[0014] According to at least one aspect of the present disclosure, a blow molded article can be obtained that can prevent the migration of wax to the surface of the blow molded article, on the premise that wax-containing polyethylene or polypropylene is used as a raw material. Also, according to at least one aspect of the present disclosure, a toner bottle can be obtained that can prevent the deterioration of the toner contained therein. Furthermore, according to at least one aspect of the present disclosure, a blow molded article can be obtained that can prevent the migration of wax to the surface of the blow molded article, on the premise that wax-containing polyethylene or polypropylene is used as a raw material. A method for producing a blow molded article capable of preventing migration of the wax to the surface of the blow molded article can be obtained, on the premise that polyethylene or polypropylene is used as a raw material. Furthermore, according to at least one aspect of the present disclosure, a molded article having a surface where migration of the wax is prevented can be obtained. Furthermore, according to at least one aspect of the present disclosure, the present disclosure is directed to providing pellets that contribute to suppression of migration of the wax to the surface of a molded article. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram of an image forming apparatus. [Diagram 2] FIG. 2 is a schematic diagram showing a method for molding a preform. [Diagram 3] FIG. 1 is a schematic diagram showing a blow molding method. [Figure 4] FIG. 1 is a schematic diagram of a one-stage blow molding process. [Diagram 5] FIG. 2 is a schematic diagram showing migration of wax-derived components. [Figure 6] FIG. 1 is a schematic diagram of a blow bottle. [Figure 7] FIG. 1 is a schematic diagram of a blow bottle. [Figure 8] FIG. 1 is a schematic diagram showing a blow molding method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, with reference to the drawings, an exemplary embodiment for carrying out the present disclosure will be described in detail. However, the scope of the present invention is not limited to the following embodiment. In this disclosure, the description "XX or more and YY or less" and "XX to YY" representing a numerical range means a numerical range including the lower limit and upper limit which are the endpoints, unless otherwise specified, and when the numerical range is described in stages, any combination of the upper limit and lower limit of each numerical range is also disclosed. In addition, in this disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.

[0017] As described above, a toner bottle (hereinafter, a recycled toner bottle) is formed using material recycled PE (hereinafter, also referred to as "MR-PE") or material recycled PP (hereinafter, also referred to as "MR-PP") obtained from a toner bottle with toner still attached thereto. When toner is stored in a toner cartridge (also called a toner cartridge), deformation occurs on the surface of the toner. The inventors speculate that the reason is as follows. That is, it is considered that the recycled toner bottle contains wax contained in the toner remaining in the toner bottle before recycling. The recycled toner bottle may also contain low molecular weight decomposition products such as wax pyrolysis products caused by the heat of the recycling process or blow molding, and further hydrolysis products caused by moisture depending on the type of wax. Hereinafter, compounds derived from wax such as wax pyrolysis products and hydrolysis products, including wax, are also referred to as wax-derived components. It is considered that at least a part of the wax-derived components is present on the inner surface of the recycled toner bottle. In particular, when the wax contains decomposition products, it is likely to migrate to the surface due to low molecular weight. It is considered that the surface of the toner particles is deformed when the toner contained in the recycled toner bottle comes into contact with the wax-derived components exposed on the inner surface. The phenomenon of deformation of the toner particle surface by wax may be referred to as chemical attack hereinafter.

[0018] As mentioned above, it is believed that chemical attacks are caused by wax-derived components derived from recycled polypropylene such as MR-PP, or wax-derived components derived from wax mixed into recycled polyethylene such as MR-PE. As shown in Figure 5, during the toner bottle molding process when PE resin or PP resin 201 reaches or exceeds its glass transition temperature, wax-derived components 202 migrate to the surface of the bottle. Above the glass transition temperature of PE resin or PP resin, thermal movement of PE resin or PP resin becomes active. As a result, PE resin or Wax-derived components migrate to the surface of the bottle through gaps in the PP resin. As mentioned above, wax-derived components have a low molecular weight and therefore tend to migrate to the surface of the molded product. Therefore, the present inventors recognized that it is necessary to develop a technology for obtaining a blow molded article that is unlikely to cause chemical attack on toner that comes into contact with its surface, even if the blow molded article is made of a resin mixture containing material recycled polyethylene or material recycled polypropylene derived from toner bottles. Based on this recognition, the present inventors conducted extensive research and found that the following blow molded article is unlikely to cause chemical attack on toner that comes into contact with its surface. That is, a blow-molded article according to at least one embodiment of the present disclosure includes at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and a wax.

[0019] As a result of the inventors' investigations, it was found that chemical attack can be prevented by having at least one selected from the group consisting of inorganic layered double hydroxides and zeolites present in polyethylene or polypropylene containing wax. The reason for this is believed to be that at least one selected from the group consisting of inorganic layered double hydroxides and zeolites (hereinafter also referred to as zeolite, etc.) adsorbs wax, suppressing the migration of wax-derived components to the surface of the toner bottle.

[0020] In particular, since toner is easily charged by friction with other members, it is believed that at least a portion of the toner remaining in the toner bottle is electrically charged. The charged state of the toner is believed to be maintained even after it becomes MR-PE or MR-PP, and it is believed that at least a portion of the wax contained in MR-PE or at least a portion of the wax contained in MR-PP is also electrically charged. It is believed that such charged wax is easily adsorbed by zeolite, etc.

[0021] Therefore, the blow molded article, molded article, and pellets according to the present disclosure contain at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax. The blow molded article can be obtained, for example, by stretch blow molding a preform as a molded article molded from a resin mixture containing at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax. The blow molded article can be obtained, for example, by blow molding pellets as a molded article molded from a resin mixture containing at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax.

[0022] (preforms, pellets) The preform (or pellets) used in blow molding preferably contains at least the following (a), (b) and (c). (a) Wax (b) at least one selected from the group consisting of inorganic layered double hydroxides and zeolites; (c) Polyethylene or polypropylene

[0023] Zeolite and the like are covered with a skin layer of polyethylene or polypropylene during molding of the bottle precursor preform (or pellet), and are therefore less likely to precipitate on the bottle surface, thus inhibiting the migration of adsorbed wax to the bottle surface. This effect makes it easier to prevent chemical attack by wax.

[0024] The polypropylene is not particularly limited, and any known polypropylene can be used. The polypropylene may be a homopolymer, a random copolymer, or The copolymer may be a block copolymer, for example, a copolymer of ethylene and propylene. The polypropylene may be recycled PP such as MR-PP, or may be virgin PP that has not undergone molecular weight reduction. However, the effect of the present disclosure is more pronounced when the PP is MR-PP obtained by recycling toner bottles. Therefore, the polypropylene is preferably material recycled polypropylene.

[0025] The PE is not particularly limited, and known polyethylene can be used. For example, the polyethylene may be at least one selected from the group consisting of HDPE (high density polyethylene), LDPE (low density polyethylene), and LLDPE (linear low density polyethylene). Preferably, the polyethylene includes HDPE (high density polyethylene). For example, KEIYO B5804 (trade name, Keiyo Polyethylene Co., Ltd.) can be used as the polyethylene.

[0026] The polyethylene may be recycled PE such as MR-PE, or may be virgin PE that has not undergone molecular weight reduction. However, the effect of the present disclosure is more pronounced when the PE is MR-PE obtained by recycling toner bottles. Therefore, the PE is preferably material recycled polyethylene.

[0027] The content of polyethylene or polypropylene in the blow molded article, molded article, pellets or preforms is not particularly limited, but is preferably 80% by mass or more, more preferably 90% by mass or more, based on the mass of the blow molded article, molded article, pellets or preforms. Also, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less. For example, it is preferably in the range of 80 to 99.9% by mass or 90 to 99.5% by mass.

[0028] The melt flow rate (MFR) of polyethylene or polypropylene is preferably 0.1 g / min to 1.0 g / 10 min, particularly preferably 0.1 g / 10 min to 0.5 g / 10 min, at 200° C. under measurement conditions conforming to Japanese Industrial Standards (JIS) K7210-1:2014. If the MFR is 0.1 g / 10 min or more, the polyethylene or polypropylene tends to be sufficiently filled during blow molding. If the MFR is 1.0 g / 10 min or less, the shape of the molded product tends to be maintained.

[0029] <Inorganic layered double hydroxide> The blow molded article, the molded article, and the pellets contain at least one selected from the group consisting of inorganic layered double hydroxides and zeolites. The presence of the inorganic layered double hydroxides and zeolites in the blow molded article, the molded article, and the pellets can be confirmed by measurement using a microscopic FT-IR.

[0030] Examples of inorganic layered double hydroxides include kaolin and mica, but as a compound that is more effective and easily available, there is a hydrotalcite compound represented by the following general formula (1): The inorganic layered double hydroxide preferably contains a hydrotalcite compound. General formula (1): M 2+ (1-X) M 3+ X (OH)2A n- (X / n) mH2O (However, 0 <X≦0.5、m≧0、M 2+ ;Mg 2+ ,Zn 2+ Divalent metal ions such as M 3+ ;Al 3+ ,Fe 3+ Trivalent metal ions such as A n- ;CO3 2- ,Cl - ,NO3 - (n-valent anions such as these, n being an integer of 1 or greater)

[0031] The hydrotalcite compound represented by the general formula (1) has a positively charged base layer [M 2+(1-X) M 3+ X (OH)2] X+ and the negatively charged intermediate layer [A n- (X / n) mH 2O] X- It is a layered compound consisting of a basic layer and an intermediate layer inserted therein, and can be considered as an intercalation compound. Intercalation compounds are generally known to exhibit unique chemical properties (reactivity). In the case of hydrotalcite compounds represented by the general formula (1), the anions (A n- It is known that the anion exchange between the base layer and anions occurs easily (anion exchange). The mechanism of anion exchange is unclear, but it is assumed to involve a combination of factors such as the electrical interaction (attraction) between the base layer and anions, the size of the voids in the intermediate layer (the thickness of the intermediate layer), and adsorption.

[0032] In the general formula (1), a divalent metal ion M 2+ As for Mg 2+ is a trivalent metal ion M 3+ As for Al 3+ As the n-valent anion, CO3 2- ,Cl - is preferred.

[0033] The content of the inorganic layered double hydroxide is preferably 0.09 to 1.2% by mass, more preferably 0.1 to 1.0% by mass, based on the mass of the blow molded product, molded product, or pellets. If it is 0.09% by mass or more, the wax can be more sufficiently adsorbed, and the wax is less likely to migrate to the bottle surface. If it is 1.2% by mass or less, the inorganic layered double hydroxide is less likely to become a starting point for rupture during blow molding. By setting the blending amount within the above range, it becomes easier to achieve both chemical attack suppression and blowability.

[0034] <Zeolite> Zeolite is a hydrated aluminosilicate containing an alkali or alkaline earth metal, consisting of a rigid anionic framework with regular channels (tubular pores) and cavities (voids). It is not particularly limited, and natural or artificial (synthetic) zeolite can be used.

[0035] Also, zeolite is preferably represented by the following composition. [Chemical formula]

[0036] M I is preferably Na + M II is preferably Ca 2+ m is preferably from 1 to 384. n is preferably from 0 to 27. There are zeolites with various framework structures. That is, as the framework structure of zeolite, there are LTA type, FER type, MWW type, MFI type, MOR type, LTL type, FAU type, BEA type, etc., which are recognized by the International Zeolite Association. In the present disclosure, zeolites with any framework structure can be used, but preferably, it is the MFI type. The MFI type (ZSM-5) is an aluminosilicate zeolite having a framework structure in which pentasil units are connected in a chain, represented by the chemical formula of the unit cell: [Na m Al m Si 96-m O 192 ·16H2O (0 < m < 27)].

[0037] The content of zeolite is preferably 0.09 to 1.2% by mass, more preferably 0.1 to 1.0% by mass, based on the mass of the blow-molded product (molded product, or pellet). When it is 0.09% by mass or more, wax can be adsorbed more sufficiently, and it becomes more difficult for wax to migrate to the bottle surface. When it is 1.2% by mass or less, zeolite is less likely to be a starting point for rupture during blow molding. By setting the blending amount within the above range, it becomes easier to balance chemical attack suppression and blowability.

[0038] From the viewpoint of achieving both chemical attack inhibition and blowability, the total content of inorganic layered double hydroxide and zeolite is 0. The content is preferably 0.09 to 1.2 mass %, and more preferably 0.1 to 1.0 mass %.

[0039] The content ratio of inorganic layered double hydroxide and zeolite in the blow molded product (molded product or pellet) can be measured by the following means. After measuring the mass of the blow molded product, the blow molded product is placed in a stainless steel container and left in an oven at 480 ° C for 1 hour to burn the resin of the blow molded product. After that, ion-exchanged water is added to the stainless steel container containing the residue and thoroughly stirred, and then filtered through a nylon mesh with an opening that does not allow the inorganic layered double hydroxide and zeolite to pass through. The opening may be selected taking into consideration the size of materials other than the inorganic layered double hydroxide and zeolite. After filtration, the moisture is removed in an oven at 100 ° C, the mass is measured, and the content ratio can be measured by subtracting the mass of the nylon mesh. In this method, the catalyst and carbon black contained in the resin pass through the nylon mesh, so the content ratio of inorganic layered double hydroxide and zeolite can be accurately measured. If the inorganic layered double hydroxide and zeolite cannot be separated by filtration alone, the content can be measured by further combining known means.

[0040] The number-average particle size of the inorganic layered double hydroxide and zeolite is preferably 0.05 to 2.00 μm, more preferably 0.10 to 1.50 μm. When the number-average particle size is 0.05 μm or more, the dispersibility in the resin is good. When the number-average particle size is 2.00 μm or less, the inorganic layered double hydroxide and zeolite are less likely to become foreign matter during blow molding, and the bursting of the molded product is easily suppressed.

[0041] <Wax> Examples of waxes include aliphatic hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, polyolefin copolymers, polyolefin wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of aliphatic hydrocarbon waxes such as oxidized polyethylene wax; or block copolymers thereof; vegetable waxes such as candelilla wax, carnauba wax, Japan wax, and jojoba wax; animal waxes such as beeswax, lanolin, and spermaceti; mineral waxes such as ozokerite, ceresin, and petrolactam; ester waxes mainly composed of aliphatic esters such as montan acid ester wax and castor wax; and aliphatic esters partially or completely deoxidized such as deoxidized carnauba wax. Further, saturated straight-chain fatty acids such as palmitic acid, stearic acid, montanic acid, or long-chain alkyl carboxylic acids having an even longer alkyl chain; unsaturated fatty acids such as brassidic acid, eleostearic acid, or valinaric acid; saturated alcohols such as stearyl alcohol, eicosyl alcohol, behenyl alcohol, carnabyl alcohol, ceryl alcohol, melissyl alcohol, or alkyl alcohols having an even longer alkyl chain; polyhydric alcohols such as sorbitol; aliphatic amides such as linoleic acid amide, oleic acid amide, or lauric acid amide; saturated aliphatic bisamides such as methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, or hexamethylene bisstearic acid amide; ethylene bis(oxalic acid)amide, ... unsaturated fatty acid amides such as m-xylene bisstearic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, and N,N'-dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide; fatty acid metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats. can be.

[0042] Among them, it is preferable that the wax contains ester wax. Ester wax is easily hydrolyzed and reduced in molecular weight during recycling and molding. Therefore, chemical attack may occur easily. Even in such a case, the blow molded article of the present disclosure can sufficiently suppress chemical attack. The hydrolyzate of the ester wax may contain a carboxyl group, but the presence of the carboxyl group makes it easy for the hydrolyzate to be ionically adsorbed on zeolite, etc., and it is considered that chemical attack can be sufficiently suppressed.

[0043] In addition, the waxes having a sharp molecular weight distribution obtained by subjecting them to a press sweating method, a solvent method, a recrystallization method, a vacuum distillation method, a supercritical gas extraction method, or a melt crystal precipitation method are preferably used, and those from which low molecular weight solid fatty acids, low molecular weight solid alcohols, low molecular weight solid compounds, and other impurities have been removed are also preferably used. The presence of wax in the blow molded article (molded article or pellets) can be confirmed by GPC-FTIR.

[0044] Specific examples of waxes include Viscol (registered trademark) 330-P, 550-P, 660-P, and TS-200 (Sanyo Chemical Industries, Ltd.), Hiwax 400P, 200P, 100P, 410P, 420P, 320P, 220P, 210P, and 110P (Mitsui Chemicals, Inc.), Sasol H1, H2, C80, C105, and C77 (Schumann-Sasol), HNP-1, HNP- 3, HNP-9, HNP-10, HNP-11, HNP-12 (Nippon Seiro Co., Ltd.), Unilin (registered trademark) 350, 425, 550, 700, Unicid (registered trademark) 350, 425, 550, 700 (Toyo Petrolite Co., Ltd.), wood wax, beeswax, rice wax, candelilla wax, and carnauba wax (available from Cerarica NODA Co., Ltd.).

[0045] The wax content in the blow molded article (molded article or pellets) is, for example, 0.001 to 0.100 mass%, 0.002 to 0.050 mass%, or 0.002 to 0.030 mass% based on the mass of the blow molded article (molded article or pellets). If the wax content is within the above range, it is possible to more reliably prevent the wax from affecting the blow moldability of the preform (or pellets). The presence and quantity of wax in the resin molded product can be determined, for example, by measurement using pyrolysis GC / MS.

[0046] In the blow molded product (molded article or pellets), the total content of the inorganic layered double hydroxide and the zeolite per 100 parts by mass of wax is preferably 400 to 5000 parts by mass, more preferably 450 to 4600 parts by mass.

[0047] The blow molded article (molded article or pellets) may contain carbon black. For example, carbon black may be added to the blow molded article for reasons of appearance. The carbon black content (blended amount) in the blow molded article (molded article or pellets) may be, for example, 0.01 to 0.20 mass%, or 0.02 to 0.10 mass%.

[0048] (Manufacturing of blow molded products) Next, one embodiment of a method for producing a blow molded product such as a toner bottle by blow molding will be described below. The means of blow molding is not particularly limited, and a known method can be used. Examples of blow molding include direct blow molding and stretch blow molding.

[0049] The blow molded article is, for example, a resin mixture containing at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax. The blow molded article can be obtained by blow molding pellets as a molded article formed from the above-mentioned. When pellets are used for blow molding, direct blow molding is preferred. That is, the method for producing a blow molded article preferably includes a step of preparing pellets containing at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax, and a molding step of blow molding the pellets to obtain a blow molded article.

[0050] Furthermore, when stretch blow molding is performed, the method for producing a blow molded article includes a step of preparing a preform containing at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax, and a molding step of stretch blow molding the preform to obtain a blow molded article.

[0051] First, an example of a method for producing pellets will be described. The pellets can also be used as a material for a preform used for biaxially stretching and blow molding a blow-molded product. For example, in the step of preparing pellets or the step of preparing a preform, at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax are melt-kneaded to form pellets. By forming the material into pellets, the material composition is made uniform, making it easier to mold. The wax may be a toner containing the wax. More specifically, at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and an electrophotographic toner containing the wax are melted and kneaded to form pellets. At least one selected from the group consisting of inorganic layered double hydroxides and zeolites may be mixed or melt-kneaded with polyethylene or polypropylene in advance to obtain a polyethylene composition or a polypropylene composition, and then a toner containing a wax may be mixed or melt-kneaded therein.

[0052] Furthermore, for example, a toner bottle containing polyethylene or polypropylene to which an electrophotographic toner containing wax is attached may be used. That is, the step of preparing the pellets preferably includes a step of pulverizing a recycled toner bottle to which an electrophotographic toner is attached to obtain a pulverized material, and a step of melting and kneading the pulverized material with at least one selected from the group consisting of inorganic layered double hydroxides and zeolites to form pellets. It is preferable that the electrophotographic toner contains wax, and the toner bottle contains polyethylene or polypropylene. The resulting pellets are subjected to blow molding such as direct blow molding to obtain a blow molded article.

[0053] In addition, when molding a preform, the following steps are preferable. That is, the step of preparing a preform preferably includes a step of pulverizing a recycled toner bottle to which electrophotographic toner is attached to obtain a pulverized material, a step of melting and kneading the pulverized material with at least one selected from the group consisting of inorganic layered double hydroxides and zeolites to form pellets, and a step of forming the preform from the formed pellets. It is also preferable that the electrophotographic toner contains wax and the toner bottle contains polyethylene or polypropylene.

[0054] The amount of electrophotographic toner is preferably 0.100 to 1.000 mass %, and more preferably 0.150 to 0.500 mass %, based on the total amount of the toner bottle and the electrophotographic toner attached to the toner bottle.

[0055] The melt-kneading means is not particularly limited, and known means such as a twin-screw extruder can be used. The temperature during melt-kneading is not particularly limited as long as the polyethylene or polypropylene can be melt-kneaded. For example, the temperature is 120 to 300° C., and preferably 180 to 240° C. The conditions for melt kneading are not particularly limited. After melt kneading, the mixture is cooled, and the melt kneaded mixture is molded into pellets that can be injection molded using a known means, such as a pelletizer.

[0056] On the other hand, when stretch blow molding is performed, the obtained pellets are used to form a preform 104 having a test tube shape by injection molding as shown in Fig. 2. Specifically, a heating cylinder 105 heats the material fed into an injection molding machine 101 to make it molten, and an extrusion screw 207 injects the molten material into preform molds 102 and 103, and after cooling, the material is removed from the mold to obtain a preform 104. In the step of preparing a preform, it is preferable to obtain a preform from the obtained pellets by injection molding. In addition, the preform preferably has a test tube shape.

[0057] Next, the molding process will be described. In the molding process, biaxial stretch blow (biaxial stretch molding) is performed on the preform 104 as shown in Fig. 3. First, the preform 104 is placed in a heating furnace 107 and heated to a temperature at which it can be stretched. The heated preform 104 is removed from the heating furnace 107 and placed in the mouth of a blow mold 108 formed by combining a left mold 108-1 and a right mold 108-2 to form a cavity therein.

[0058] It is preferable to place the heated preform at the mouth of the blow mold in a short time (for example, within 10 seconds) so that the temperature of the preform does not drop before the start of the biaxial stretching step. The heated preform placed in the blow mold 108 is stretched in the vertical direction using a stretch rod 109. This stretching is called the first stretching. In the first stretching, it is preferable to inject gas so that the preform 104 does not come into contact with the stretch rod 109, and the pressure of the gas at this time is called the first blow pressure.

[0059] After the first stretching, gas 110 is introduced from the preform mouth 106 to expand the preform in the lateral direction (circumferential direction). This is called the second stretching. The pressure of the gas at this time is called the second blow pressure. Examples of the gas to be blown include air, nitrogen, carbon dioxide, and argon.

[0060] By carrying out these primary and secondary stretching steps, preform 104 expands in each direction indicated by arrows 301 and adheres to the inner wall of blow mold 108, and is cooled and solidified in this state to become blow-molded product 112. The molding process preferably includes a step of stretching the preform in the longitudinal direction of the preform using a stretching rod, and a step of injecting gas into the preform stretched in the longitudinal direction to stretch the preform in the circumferential direction. Next, the left mold 108-1 and the right mold 108-2 of the blow mold 108 are separated, and the blow-molded article 112 is removed from the blow mold 108. Since this blow-molded article 112 is stretched in both the vertical and horizontal directions, it becomes a molded article with high strength.

[0061] Thus, it is preferable that the preform is not crystallized (non-crystalline, i.e., amorphous) during the stretching step of injection stretch blow molding. If the preform is in an amorphous state and reaches the blow molding temperature, the resin will stretch and crystallize in the stretched direction by blowing, i.e., biaxial stretch molding, and a bottle with high strength can be formed.

[0062] There are two types of injection stretch blow molding: one-stage and two-stage. The one-stage method uses the residual heat of the preform immediately after it is removed from the mold to stretch blow mold it as is, or after adjusting the temperature. The two-stage method cools the preform down to room temperature, and then stretch blow molds it again after adjusting the temperature.

[0063] In the one-stage method, as shown in FIG. 4, a preform 104 is injected from an injection molding machine 101. After molding, cooling is completed in a short time of 10 seconds or less during injection molding so that the preform 104 does not fall below the glass transition temperature of the polyethylene or polypropylene. Then, the preform is immediately heated and kept at a blow molding temperature (for example, 130°C to 170°C) and blow molded to obtain a blown bottle 112. An apparatus in which the injection molding apparatus and the blow molding apparatus are integrated is used.

[0064] The two-stage method is a method in which, after injection molding a preform, the preform is cooled to below the glass transition temperature of the polyethylene or polypropylene, removed, and then heated to the blow molding temperature (for example, 130°C to 170°C) in a separate blow molding machine for blow molding. A machine with separate injection molding machine and blow molding machine is used. For example, after molding the preform in the preform preparation process, the preform is cooled to below the glass transition temperature of the polyethylene or polypropylene, and then the molding process is carried out.

[0065] The one-stage method is preferable because it does not cool the preform below its glass transition temperature and therefore requires less energy to reheat than the two-stage method.

[0066] Next, a method using direct blow molding will be described as one embodiment of a method for producing a blow molded article. The means for direct blow molding the pellets is not particularly limited, and known methods can be adopted. A known direct blow molding machine can be used for direct blow molding. The extrusion temperature and the like can be appropriately set according to the polyethylene or polypropylene used. Specifically, for example, the following methods can be mentioned. The pellets obtained by the above method are fed into an injection molding machine 801. A heating cylinder 802 heats the material fed into the injection molding machine 801 to make it molten, and an extrusion screw 803 sends the molten material to a head 804. The molten material then sags down between the molds 805 under its own weight. The resin sagging under its own weight is then sandwiched between the molds 805 from both sides, and gas is introduced from a blow pin 806 to make the resin adhere to the inner wall of the mold 805. In this state, the resin is cooled and solidified, and a blow-molded product is obtained.

[0067] Next, a method for checking chemical attack in a toner bottle obtained by blow molding such as biaxial stretch blow molding or direct blow molding will be described. Toner is placed in a toner bottle obtained by blow molding. The toner bottle containing the toner is left in the usage environment. For the chemical attack evaluation, the usage environment is set at 50°C for 72 hours, and the toner bottle is left in a test thermostatic chamber. The toner bottle exposed to the usage environment is removed, and the toner adhering to the inner surface of the bottle is removed. The toner is discharged from the bottle by turning the toner storage opening of the bottle upside down, and the toner adhering to the inner surface of the bottle is attached with adhesive tape or the like, allowing the toner to be easily removed. When the extracted toner is observed under an electron microscope or the like to observe deformation of the toner particle surface, traces of deformation can be observed on the contact surface of the toner bottle of the toner particles that have been subjected to chemical attack.

[0068] (Image forming device) The image forming apparatus will be described below with reference to the drawings. Fig. 1 is a schematic diagram showing a four-color image forming apparatus using an electrophotographic method, with 80 being the main body of the image forming apparatus. This image forming apparatus 80 is configured as a so-called intermediate transfer tandem type image forming apparatus in which four color image forming units are arranged side by side on an intermediate transfer belt.

[0069] In the image forming apparatus 80, image formation is performed as follows: First, in the image forming apparatus 80, an electrostatic latent image is formed on the photosensitive drum 17 (17y, 17m, 17c, 17bk) by the exposure device 50 (50y, 50m, 50c, 50bk) based on print data. In the image forming apparatus 80, the formed electrostatic latent image is developed by the developing device 21 (21y, 21m, 21c, 21bk) to form a toner image.

[0070] In this image forming apparatus 80, the toner image is transferred onto an intermediate transfer body 62 by a primary transfer device 60 (60y, 60m, 60c, 60bk), and then transferred onto a sheet material S supplied from a paper feeder 63 by a secondary transfer section 64 (64a, 64b). Next, in this image forming apparatus 80, the toner image transferred onto the sheet S is fixed onto the sheet material S by a fixing means 68, and then the sheet material S is discharged onto a paper discharge tray 70.

[0071] In addition, in this image forming apparatus 80, a toner image is formed by the developing device 21, and detachable toner bottles 3 (3Y, 3M, 3C, 3Bk) are used to supply toner to the developing device 21. The toner bottle according to at least one embodiment of the present disclosure is a toner bottle used in this manner. The toner bottle contains at least one selected from the group consisting of inorganic layered double hydroxides and zeolites, polyethylene or polypropylene, and wax. EXAMPLES

[0072] The present disclosure will be described in detail below using examples and comparative examples. However, the present disclosure is not limited to these examples. In the following examples and comparative examples, "%" means "mass %" unless otherwise specified.

[0073] <Making toner bottles using stretch blow molding> A one-stage blow molding machine (ASB-70DPH manufactured by Nissei ASB Machinery Co., Ltd.) was used to produce a toner bottle 3 (total length 439.5 mm, diameter 101 mm) shown in Figure 6. The blow stretching ratio was set to "vertical ratio x horizontal ratio = 6.7". The "longitudinal ratio" of the blow stretch ratio is a value calculated by dividing the "total length after stretching" by the "total length (before stretching) of the part (heated part) of the preform that reaches the stretching temperature." The "lateral ratio" of the blow stretch ratio is a value calculated by dividing the "diameter of the middle part after stretching" by the "diameter of the middle part of the preform (before stretching)".

[0074] First, the materials shown in Table 1 below were melt-kneaded and then pelletized to prepare a master batch with a carbon black concentration of 5 mass %. [Table 1]

[0075] Next, the master batch with a carbon black concentration of 5% by mass prepared above and PP were mixed in the ratio shown in Table 2 below, melt-kneaded, and then pelletized to obtain pellets of a resin mixture. [Table 2]

[0076] <Stretch blow molding conditions> The pellets of the resin mixture dried above were fed into an injection molding device of a one-step stretch blow molding machine (product name: ASB-70DPH; manufactured by Nissei ASB Machinery Co., Ltd.), and a toner bottle was molded by biaxial stretch blow molding. The one-step stretch blow molding machine can continuously carry out (one-stage method) a process of obtaining a test tube-shaped preform by injection molding, and a process of obtaining a bottle-shaped molded product by biaxial stretch blow molding of the preform. The screw diameter of the injection molding machine in the molding machine was 54 mm.

[0077] First, a mold capable of molding a preform having an outer diameter of 30 mm, a wall thickness of 3.7 mm, and a length of 220 mm was prepared as a mold for molding a preform. Then, a preform was molded under the following molding conditions. Screw diameter: 54mm Screw position before filling the cavity with resin mixture: 95mm ·Injection speed Up to 5mm of screw advance: 50% of maximum speed Advance the screw another 20mm: 30% of maximum speed Until the screw advances another 35mm: 25% of maximum speed PV switching position: 35mm First stage of pressure retention 30MPa, 4s Second stage of pressure retention 20MPa, 7.99s ·Heating tube temperature: 230℃ ·Cooling time: 10.0 seconds Mold temperature: 20℃

[0078] After a cooling time of 10.0 seconds had elapsed, the preform was demolded and transported to the biaxial stretch blow station of the one-step stretch blow molding machine. The temperature of the preform during transportation was controlled as follows. Preform heating temperature 10% of the preform's total length from the top of the preform 180℃ 25% of the preform's total length from the top of the preform 200℃ 50% of the preform's total length from the top of the preform 200℃ 75% of the preform's total length from the top of the preform 140℃ Next, the preform adjusted to the above temperature was placed in a cylindrical mold adjusted to a temperature of 20°C and having a size corresponding to the size of the toner bottle, and was subjected to biaxial stretch blow molding to produce a blown bottle. The preform was heated during transportation, so that the surface temperature of the center of the preform immediately before being placed in the cylindrical mold was 150°C.

[0079] First, the stretch bar was inserted from the retreated position into the preform through the opening of the preform and advanced until it contacted the top of the preform. Next, the air pressure driving the stretch bar was set to 1.2 MPa and the stretch bar was advanced further. Next, 0.5 seconds after the start of the further advancement of the stretch bar, primary air was introduced into the preform through the opening of the preform. The pressure of the primary air was set to 0.4 MPa. Next, 0.7 seconds after the introduction of the primary air, secondary air was introduced. The pressure of the secondary air was set to 1.2 MPa. Then, air was introduced into the preform for 2.7 seconds from the start of the introduction of the primary air. Next, the pressure inside the preform was returned to normal pressure over 0.5 seconds. In this way, a toner bottle was produced by blow molding. This bottle is a toner bottle using virgin PP that has not been recycled. Using the above method, 200 toner bottles were produced using virgin PP.

[0080] (Example A1-1) <Production of recycled pellets> All of the 200 toner bottles prepared above, including virgin PP, were filled with black toner contained in a toner cartridge (product name: Toner NPG-26, manufactured by Canon Inc.). The black toner contained ester wax. After that, the opening of the toner bottle made of virgin PP was turned vertically downward to discharge the black toner inside. Even after this operation, a small amount of black toner was attached to the inner wall of each toner bottle. At this time, the average amount of black toner remaining in the toner bottle for the 200 toner bottles was 0.321% by mass based on the mass of the toner bottle body. Note that the mass of the toner bottle body here refers to the mass of the toner bottle and only the toner remaining inside it, after all the supply parts and the like attached to the toner bottle have been removed. In the following examples, the meaning of "mass of the toner bottle body" is the same. Next, each toner bottle was crushed into pieces of about 5 to 10 mm square using a crusher to obtain crushed products (hereinafter also referred to as "flake products"). The wax content of the obtained flake products was measured using GPC and FT-IR, and was found to be 0.022 parts by mass per 100 parts by mass of the flake products. To 99.5% by mass of this flake product, 0.5% by mass of a hydrotalcite compound (trade name: DHT-4C; manufactured by Kyowa Chemical Industry Co., Ltd.) was added as an inorganic layered double hydroxide, and the mixture was melt-kneaded using a twin-screw extruder (manufactured by Ikegai Co., Ltd., PC-46) at a temperature of 210°C, a screw rotation speed of 200 rpm, and a discharge rate of 50 kg / h, and then pelletized. The inorganic layered double hydroxide used here was in the form of a filler, with a number-average particle size of 0.38 μm. (This recycled material is referred to as MR-PP (1-1)).

[0081] <Making blow bottles> The MR-PP (1-1) was placed in the one-step stretch blow molding machine and biaxial stretch blow molding was performed under the same blow molding conditions as described above (the obtained toner bottle is referred to as toner bottle (A1-1)). Toner was placed in the toner bottle (A1-1) and a chemical attack confirmation test was performed in an environment of 50°C for 72 hours. As a result, no deformation of the toner particle surface was confirmed even when observing the toner attached to the inner surface of the toner bottle.

[0082] Toner bottles (A1-2), (A1-3), and a comparative toner bottle (A1-4) were obtained by blow molding in the same manner as in Example A1-1, except that the compounding ratio of the flakes and the inorganic layered double hydroxide (hydrotalcite compound) was changed as shown in Table 3. Blow molding could be performed without any problems for all of the toner bottles. For each of the obtained toner bottles, the deformation of the toner particle surface was observed in the same manner as in Example A1-1. [Table 3]

[0083] Toner bottle (A1-2) When the amount of inorganic layered double hydroxide added was 1.0 mass%, a biaxial stretch blow molding of the preform was performed, and blow molding was possible. When this toner bottle (A1-2) was used to evaluate chemical attack, no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0084] Toner bottle (A1-3) When the amount of inorganic layered double hydroxide added was 0.1% by mass, biaxial stretch blow molding of the preform was performed, and blow molding was possible without any problems. When this toner bottle (A1-3) was used to evaluate chemical attack, no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0085] Comparison toner bottle (A1-4) When the preform was subjected to biaxial stretch blow molding with the inorganic layered double hydroxide added at 0.0% by mass, blow molding was possible without any problems. When chemical attack was evaluated using this comparative toner bottle (A1-4), deformation was confirmed on the surface of the toner particles adhering to the inner surface of the toner bottle, and chemical attack had occurred. The reason for this is thought to be that if inorganic layered double hydroxide is not added, the wax, which is the cause of chemical attack, is not adsorbed by the inorganic layered double hydroxide, and the wax migrates to the inner surface of the toner bottle, causing chemical attack.

[0086] (Example A2-1) <Production of recycled pellets> 0.5% by mass of zeolite (product name: Silton MT-8000, manufactured by Mizusawa Chemical Industries, Ltd.) was added to 99.5% by mass of flakes prepared in the same manner as in Example A1-1, and the mixture was melt-kneaded at a temperature of 210°C, a screw speed of 200 rpm, and a discharge rate of 50 kg / h using a twin-screw extruder (product name: PC-46; manufactured by Ikegai Co., Ltd.), and then pelletized. The zeolite used here was in the form of a filler. (This recycled material is referred to as MR-PP (2-1)).

[0087] <Making blow bottles> The MR-PP (2-1) was placed in the one-step stretch blow molding machine and biaxial stretch blow molding was performed under the same blow molding conditions as described above (the obtained toner bottle is referred to as toner bottle (A2-1)). Toner was placed in the toner bottle (A2-1) and a chemical attack confirmation test was performed in an environment of 50°C for 72 hours. As a result, no deformation of the toner particle surface was confirmed even when observing the toner attached to the inner surface of the toner bottle.

[0088] Toner bottles (A2-2), (A2-3), and a comparative toner bottle (A2-4) were obtained by blow molding in the same manner as in Example A2-1, except that the compounding ratio of the flakes and zeolite was changed as shown in Table 4. Blow molding could be performed without any problems for all of the toner bottles. For each of the obtained toner bottles, the deformation of the toner particle surface was observed in the same manner as in Example A2-1. [Table 4]

[0089] Toner bottle (A2-2) When the amount of zeolite added was 1.0 mass%, the preform was subjected to biaxial stretch blow molding, and the blow molding was possible without any problems. When the toner attached to the inner surface of the toner bottle was observed to evaluate chemical attack, no deformation of the toner particle surface was confirmed.

[0090] Toner bottle (A2-3) When the amount of zeolite added was 0.1% by mass, the preform was subjected to biaxial stretch blow molding, and the blow molding was possible without any problems. When the toner attached to the inner surface of the toner bottle was observed to evaluate chemical attack, no deformation of the toner particle surface was confirmed.

[0091] Comparison toner bottle (A2-4) When the preform was biaxially stretched and blow molded with 0.0% by mass of added zeolite, blow molding was possible without any problems. When chemical attack was evaluated using this comparative toner bottle (A2-4), deformation was confirmed on the surface of the toner particles attached to the inner surface of the toner bottle, and chemical attack had occurred. The reason for this is thought to be that if zeolite is not added, the wax, which is the cause of chemical attack, is not adsorbed by the zeolite, and the wax migrates to the inner surface of the toner bottle, causing chemical attack.

[0092] <Manufacturing toner bottles by direct blowing> A direct blow molding machine (model name: MSE-55E / 54M-AP(E2); manufactured by Tahara Co., Ltd.) was used to produce a toner bottle 3 shown in Fig. 7. In Fig. 7, A was φ76 mm and B was 150 mm.

[0093] First, the materials shown in Table 1 below were melt-kneaded and then pelletized to prepare a master batch with a carbon black concentration of 5 mass %. [Table 5]

[0094] Next, the master batch with a carbon black concentration of 5% by mass prepared above and PP were mixed in the ratio shown in Table 2 below, melt-kneaded, and then pelletized to obtain pellets of a resin mixture. [Table 6]

[0095] <Direct blow molding conditions> The pellets of the resin mixture dried above were put into a direct blow molding machine and molded into a toner bottle under the following conditions: The screw diameter of the molding machine was 50 mm.

[0096] Direct blow molding was performed under the following molding conditions. Screw diameter: 50mm Cylinder temperature: 210℃ -Extrusion rate 10kg / h Blow pressure: 0.6MPa Cooling time: 15s Mold temperature: 15℃ A toner bottle was produced by the above-mentioned direct blow molding. This toner bottle is made of virgin PP that has not been recycled. Using the above method, 200 toner bottles were produced using virgin PP.

[0097] (Example A3-1) <Production of recycled pellets> In the same manner as in Example A1-1, 200 toner bottles using virgin PP with black toner remaining inside were prepared. The amount of black toner remaining in the toner bottles was 0.321% by mass, based on the mass of the toner bottle body, as the average value for the 200 toner bottles. Next, 200 of the toner bottles with residual toner inside were crushed into pieces of about 5 to 10 mm square using a crusher to obtain crushed products (hereinafter also referred to as "flake products"). The wax content of the obtained flake products was measured using GPC and FT-IR, and was found to be 0.022 parts by mass per 100 parts by mass of the flake products. To 99.5% by mass of this flake product, 0.5% by mass of a hydrotalcite compound (trade name: DHT-4C; manufactured by Kyowa Chemical Industry Co., Ltd.) was added as an inorganic layered double hydroxide, and the mixture was melt-kneaded using a twin-screw extruder (manufactured by Ikegai Co., Ltd., PC-46) at a temperature of 210°C, a screw rotation speed of 200 rpm, and a discharge rate of 50 kg / h, and then pelletized. The granular double hydroxide was in the form of a filler, and had a number-average particle size of 0.38 μm. (This recycled material is referred to as MR-PP (3-1)).

[0098] <Making blow bottles> The MR-PP (3-1) was placed in the direct blow molding machine and subjected to direct blow molding under the same blow molding conditions as described above (the obtained toner bottle is referred to as toner bottle (A3-1)). Toner was placed in the toner bottle (A3-1) and a chemical attack confirmation test was carried out in an environment of 50°C for 72 hours. As a result, no deformation of the toner particle surface was confirmed even when observing the toner attached to the inner surface of the toner bottle.

[0099] Toner bottles (A3-2), (A3-3), and a comparative toner bottle (A3-4) were obtained by blow molding in the same manner as in Example A3-1, except that the compounding ratio of the flakes and the inorganic layered double hydroxide (hydrotalcite compound) was changed as shown in Table 3. Blow molding could be performed without any problems for all of the toner bottles. For each of the obtained toner bottles, the deformation of the toner particle surface was observed in the same manner as in Example A3-1. [Table 7]

[0100] Toner bottle (A3-2) When direct blow molding was performed with an inorganic layered double hydroxide content of 1.0% by mass, blow molding was possible without any problems. When chemical attack was evaluated using this toner bottle (A3-2), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0101] Toner bottle (A3-3) When direct blow molding was performed with an inorganic layered double hydroxide content of 0.1% by mass, blow molding was possible without any problems. When chemical attack was evaluated using this toner bottle (A3-3), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0102] Comparison toner bottle (A3-4) When direct blow molding was performed with an added amount of inorganic layered double hydroxide of 0.0% by mass, blow molding was possible without any problems. When chemical attack was evaluated using this comparative toner bottle (A3-4), deformation was confirmed on the surface of the toner particles attached to the inner surface of the toner bottle, and chemical attack had occurred. The reason for this is thought to be that if inorganic layered double hydroxide is not added, the wax, which is the cause of chemical attack, is not adsorbed by the inorganic layered double hydroxide, and the wax migrates to the inner surface of the toner bottle, causing chemical attack.

[0103] (Example A4-1) <Production of recycled pellets> 0.5% by mass of zeolite (product name: Silton MT-8000, manufactured by Mizusawa Industrial Chemicals Co., Ltd.) was added to 99.5% by mass of flakes prepared in the same manner as in Example A3-1, and the mixture was melt-kneaded at a temperature of 210°C, a screw rotation speed of 200 rpm, and a discharge rate of 50 kg / h using a twin-screw extruder (PC-46, manufactured by Ikegai Co., Ltd.), and then pelletized. The zeolite used here was in the form of a filler. (This recycled material is referred to as MR-PP (4-1)).

[0104] <Making blow bottles> The MR-PP (4-1) was placed in the direct blow molding machine and subjected to direct blow molding under the same blow molding conditions as described above (the obtained toner bottle is referred to as toner bottle (A4-1)). Toner was placed in the toner bottle (A4-1) and a chemical attack confirmation test was carried out in an environment of 50°C for 72 hours. As a result, no deformation of the toner particle surface was confirmed even when observing the toner attached to the inner surface of the toner bottle.

[0105] Toner bottles (A4-2), (A4-3) and a comparative toner bottle (A4-4) were obtained by blow molding in the same manner as in Example A4-1, except that the compounding ratio of the flakes and zeolite was changed as shown in Table 8. Blow molding could be performed without any problems for all of the toner bottles. For each of the obtained toner bottles, the deformation of the toner particle surface was observed in the same manner as in Example A4-1. [Table 8]

[0106] Toner bottle (A4-2) When direct blow molding was performed with an added amount of 1.0 mass% zeolite, blow molding was possible without any problems. When chemical attack evaluation was performed using this toner bottle (A4-2), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0107] Toner bottle (A4-3) When direct blow molding was performed with an added amount of 0.1% by mass of zeolite, blow molding was possible without any problems. When chemical attack evaluation was performed using this toner bottle (A4-3), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0108] Comparison toner bottle (A4-4) When direct blow molding was performed with 0.0% by mass of zeolite added, blow molding was possible without any problems. When chemical attack was evaluated using this comparative toner bottle (A4-4), deformation was observed on the surface of the toner particles adhering to the inner surface of the toner bottle. The reason for this is thought to be that if zeolite is not added, the wax, which is the cause of chemical attack, is not adsorbed by the zeolite, and the wax migrates to the inner surface of the toner bottle, causing chemical attack.

[0109] <Manufacturing toner bottles by direct blowing> A toner bottle 3 shown in FIG. 7 was produced using a direct blow molding device. A was 76 mm in diameter, and B was 150 mm in diameter. KEIYO B5804 (product name) manufactured by Keiyo Polyethylene Co., Ltd. was used as the pellet material.

[0110] <Direct blow molding conditions> The pellets of the resin mixture dried above were fed into a direct blow molding machine (model name: MSE-55E / 54M-AP(E2), Tahara Co., Ltd.) to mold a toner bottle. The screw diameter of the injection molding machine in the molding machine was 50 mm.

[0111] Direct blow molding was performed under the following molding conditions. Extruder screw diameter: 50mm Extruder cylinder temperature: 182℃ -Extrusion rate 10kg / h Blow pressure: 0.6MPa Cooling time: 15s Mold temperature: 15℃ A toner bottle was produced by the above direct blow molding. This toner bottle is made of virgin PE that has not been recycled. Using the above method, 200 toner bottles were produced using virgin PE.

[0112] (Example B1-1) <Production of recycled pellets> All 200 toner bottles containing virgin PE prepared above were filled with black toner contained in a toner cartridge (product name: Toner NPG-26, manufactured by Canon Inc.). The black toner contained ester wax. Next, the opening of the toner bottle using virgin PE was turned vertically downward to discharge the black toner inside. Even after this operation, a small amount of black toner was still attached to the inner wall of each toner bottle. At this time, the amount of black toner remaining in the toner bottle was 0.321% by mass, based on the mass of the toner bottle itself, on the average of the 200 toner bottles. Note that the mass of the toner bottle itself here refers to the mass of the toner bottle and only the toner remaining inside it, after all the supply parts and the like attached to the toner bottle have been removed (hereinafter, Same as below).

[0113] Next, each toner bottle was crushed into pieces of about 5 to 10 mm square using a crusher to obtain crushed products (hereinafter also referred to as "flake products"). The wax content of the obtained flake products was measured using GPC and FT-IR, and was found to be 0.022 parts by mass per 100 parts by mass of the flake products. To 99.5% by mass of this flake product, 0.5% by mass of a hydrotalcite compound (trade name: DHT-4C; manufactured by Kyowa Chemical Industry Co., Ltd.) was added as an inorganic layered double hydroxide, and the mixture was melt-kneaded using a twin-screw extruder (manufactured by Ikegai Co., Ltd., PC-46) at a temperature of 200°C, a screw rotation speed of 200 rpm, and a discharge rate of 50 kg / h, and then pelletized. The inorganic layered double hydroxide used here was in the form of a filler, with a number-average particle size of 0.38 μm. (This recycled material is referred to as MR-PE (1-1)).

[0114] <Making blow bottles> The MR-PE (1-1) was put into the direct blow molding machine and direct blow molding was performed under the same blow molding conditions as described above (the obtained toner bottle is referred to as toner bottle (B1-1)). Toner was placed in the toner bottle (B1-1) and a chemical attack confirmation test was performed in an environment of 50°C for 72 hours. As a result, no deformation of the toner particle surface was confirmed even when observing the toner attached to the inner surface of the toner bottle.

[0115] Toner bottles (B1-2), (B1-3), and a comparative toner bottle (B1-4) were obtained by blow molding in the same manner as in Example B1-1, except that the compounding ratio of the flakes and the inorganic layered double hydroxide (hydrotalcite compound) was changed as shown in Table 1. Blow molding could be performed without any problems for all of the toner bottles. For each of the obtained toner bottles, the deformation of the toner particle surface was observed in the same manner as in Example B1-1. [Table 9]

[0116] Toner bottle (B1-2) When direct blow molding was performed with an inorganic layered double hydroxide content of 1.0% by mass, blow molding was possible without any problems. When chemical attack was evaluated using this toner bottle (B1-2), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0117] Toner bottle (B1-3) When direct blow molding was performed with an inorganic layered double hydroxide content of 0.1% by mass, blow molding was possible without any problems. When chemical attack was evaluated using this toner bottle (B1-3), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0118] Comparison toner bottle (B1-4) When direct blow molding was performed with an added amount of inorganic layered double hydroxide of 0.0% by mass, blow molding was possible without any problems. When chemical attack was evaluated using this comparative toner bottle (B1-4), deformation was confirmed on the surface of the toner particles attached to the inner surface of the toner bottle, and chemical attack had occurred. The reason for this is thought to be that if inorganic layered double hydroxide is not added, the wax, which is the cause of chemical attack, is not adsorbed by the inorganic layered double hydroxide, and the wax migrates to the inner surface of the toner bottle, causing chemical attack.

[0119] (Example B2-1) <Production of recycled pellets> 0.5% by mass of zeolite (product name: Silton MT-8000, manufactured by Mizusawa Industrial Chemicals) was added to 99.5% by mass of the flakes prepared in the same manner as in Example B1-1, and the mixture was subjected to a biaxial extrusion. The mixture was melt-kneaded at 200°C, a screw speed of 200 rpm, and a discharge rate of 50 kg / h using a pelletizer (PC-46 manufactured by Ikegai Corporation), and then pelletized. The zeolite used here was in the form of a filler. (This recycled material is referred to as MR-PE (2-1)).

[0120] <Making blow bottles> The MR-PE (2-1) was put into the direct blow molding machine and direct blow molding was performed under the same blow molding conditions as described above (the obtained toner bottle is referred to as toner bottle (B2-1)). Toner was placed in the toner bottle (B2-1) and a chemical attack confirmation test was performed in an environment of 50°C for 72 hours. As a result, no deformation of the toner particle surface was confirmed even when observing the toner attached to the inner surface of the toner bottle.

[0121] Toner bottles (B2-2), (B2-3), and a comparative toner bottle (B2-4) were obtained by blow molding in the same manner as in Example B2-1, except that the compounding ratio of the flakes and zeolite was changed as shown in Table 2. Blow molding could be performed without any problems for all of the toner bottles. For each of the obtained toner bottles, the deformation of the toner particle surface was observed in the same manner as in Example B2-1. [Table 10]

[0122] Toner bottle (B2-2) When direct blow molding was performed with an added amount of 1.0 mass% zeolite, blow molding was possible without any problems. When chemical attack evaluation was performed using this toner bottle (B2-2), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0123] Toner bottle (B2-3) When direct blow molding was performed with an added amount of 0.1% by mass of zeolite, blow molding was possible without any problems. When chemical attack evaluation was performed using this toner bottle (B2-3), no deformation of the toner particle surface was confirmed even when observing the toner adhering to the inner surface of the toner bottle.

[0124] Comparison toner bottle (B2-4) When direct blow molding was performed with 0.0% by mass of zeolite added, blow molding was possible without any problems. When chemical attack was evaluated using this comparative toner bottle (B2-4), deformation was confirmed on the surface of the toner particles attached to the inner surface of the toner bottle, and chemical attack had occurred. The reason for this is thought to be that if zeolite is not added, the wax, which is the cause of chemical attack, is not adsorbed by the zeolite, and the wax migrates to the inner surface of the toner bottle, causing chemical attack.

[0125] The present disclosure relates to the following configurations or methods. (Configuration 1) A blow molded article, The blow molded article is At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A blow molded article comprising: (Configuration 2) 2. The blow-molded article according to claim 1, wherein the total content of the inorganic layered double hydroxide and the zeolite is 0.09 to 1.2% by mass based on the mass of the blow-molded article. (Configuration 3) 3. The blow molded article according to claim 1 or 2, wherein the inorganic layered double hydroxide comprises a hydrotalcite compound. (Configuration 4) The blow molded article according to any one of configurations 1 to 3, wherein the polyethylene or polypropylene is material recycled polyethylene or material recycled polypropylene. (Configuration 5) 5. The blow molded article according to any one of claims 1 to 4, wherein the wax comprises an ester wax. (Configuration 6) 6. The blow molded article according to any one of configurations 1 to 5, wherein the blow molded article is a toner bottle. (Configuration 7) A toner bottle, The toner bottle is At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A toner bottle comprising: (Method 8) A method for producing the blow molded article according to any one of configurations 1 to 6, A step of preparing a preform containing at least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite, the polyethylene or polypropylene, and the wax; and A method for producing a blow molded article, comprising a molding step of stretch blow molding the preform to obtain the blow molded article. (Method 9) The step of preparing the preform comprises: A step of crushing the recycled toner bottles to which electrophotographic toner has been attached to obtain crushed material; A step of melting and kneading the ground product with at least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite to form pellets; and forming the preform from the formed pellet; the electrophotographic toner comprises the wax, The method for producing a blow-molded article according to Method 8, wherein the toner bottle comprises the polyethylene or polypropylene. (Method 10) A method for producing the blow molded article according to any one of configurations 1 to 6, At least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite; preparing pellets containing the polyethylene or polypropylene and the wax; and A method for producing a blow-molded article, comprising a molding step of blow-molding the pellets to obtain the blow-molded article. (Method 11) The step of preparing the pellets comprises: The method includes a step of pulverizing a recycled toner bottle to which electrophotographic toner has been attached to obtain a pulverized material, and a step of melting and kneading the pulverized material with at least one selected from the group consisting of inorganic layered double hydroxides and zeolites to form pellets, the electrophotographic toner comprises the wax, 11. The method for producing a blow molded article according to method 10, wherein the toner bottle comprises the polyethylene or polypropylene. (Configuration 12) A molded article, comprising: At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A molded article comprising: (Configuration 13) At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A pellet comprising: [Explanation of symbols]

[0126] 3: toner bottle, 21: developing device, 80: image forming device, 60: primary transfer device, 62: intermediate transfer body, 63: paper feeder, 64: secondary transfer section, 68: fixing means, 70: paper discharge tray, 101: injection molding machine, 102: preform mold, 103: preform mold, 104: preform, 105: heating cylinder, 106: preform mouth, 107: heating furnace, 108: blow mold, 109: stretch rod, 110: gas, 112: blow molded product, 201: PP resin, 202: wax-derived component, 207: extrusion screw

Claims

1. A blow molded article, The blow molded article is At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A blow molded article comprising:

2. 2. The blow molded article according to claim 1, wherein the total content of the inorganic layered double hydroxide and the zeolite is 0.09 to 1.2 mass% based on the mass of the blow molded article.

3. The blow molded article according to claim 1 , wherein the inorganic layered double hydroxide comprises a hydrotalcite type compound.

4. The blow molded article according to claim 1 , wherein the polyethylene or polypropylene is material recycled polyethylene or material recycled polypropylene.

5. The blow molded article of claim 1 , wherein the wax comprises an ester wax.

6. The blow molded article according to claim 1 , wherein the blow molded article is a toner bottle.

7. A toner bottle, The toner bottle is At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A toner bottle comprising:

8. A method for producing a blow molded article according to any one of claims 1 to 6, A step of preparing a preform containing at least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite, the polyethylene or polypropylene, and the wax; and A method for producing a blow molded article, comprising a molding step of stretch blow molding the preform to obtain the blow molded article.

9. The step of preparing the preform comprises: A step of crushing the recycled toner bottles to which electrophotographic toner has been attached to obtain crushed material; A step of melting and kneading the ground product with at least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite to form pellets; and forming the preform from the formed pellet; the electrophotographic toner comprises the wax, The method for producing a blow molded article according to claim 8, wherein the toner bottle comprises the polyethylene or polypropylene.

10. A method for producing a blow molded article according to any one of claims 1 to 6, preparing pellets containing at least one selected from the group consisting of the inorganic layered double hydroxide and the zeolite, the polyethylene or polypropylene, and the wax; and A method for producing a blow-molded article, comprising a molding step of blow-molding the pellets to obtain the blow-molded article.

11. The step of preparing the pellets comprises: The method includes a step of pulverizing a recycled toner bottle to which electrophotographic toner has been attached to obtain a pulverized material, and a step of melting and kneading the pulverized material with at least one selected from the group consisting of inorganic layered double hydroxides and zeolites to form pellets, the electrophotographic toner comprises the wax, The method for producing a blow molded article according to claim 10, wherein the toner bottle comprises the polyethylene or polypropylene.

12. A molded article, comprising: At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A molded article comprising:

13. At least one selected from the group consisting of inorganic layered double hydroxides and zeolites; Polyethylene or polypropylene; Wax and A pellet comprising:

Citation Information

Patent Citations

  • Polypropylene composition for blow holding and molded item made thereof

    JP2000178390A

  • Plastic-molded article comprising regenerated plastic and elastic polymer

    JP2009001693A

  • Toner container and manufacturing method thereof

    JP2010260638A